Participants' decision to enroll in cohort studies with biobanks: quantitative insights from two German studies. (November 2017) - Nobile, Hélène; Borry, Pascal; Pischon, Tobias; Steinbrecher, Astrid; Boeing, Heiner; Vigl, Matthäus; Bergmann, Manuela M
Aim: To understand participants' actual motivations to enroll in cohort studies with biobanks.Methods: Participants of two such studies currently ongoing in Germany were invited to fill in a questionnaire about their decision to enroll.Results: From the 623 questionnaires completed, contributing to scientific knowledge appeared as a main motive for enrollment, followed by learning about personal health status and receiving personal medical advice.Conclusion: Motivating participation as a way to contribute to the common good rather than as a way to obtain personal benefits appears to be particularly appropriate to ensure participants' long-term commitment and should therefore be further investigated in this setting.